2002
DOI: 10.1039/b210061d
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble stilbene dendrimers

Abstract: The third generation of novel photo-responsive water-soluble stilbene dendrimer (trans- and cis-G3 WSD) undergoes unusual one-way trans-to-cis isomerization to give 100% of cis isomer at the photostationary state on UV irradiation in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…7). Water-soluble dendrimers with photoresponsive core have already been studied [61][62][63][64][65][66]. It was found that the poly aryl(ether) dendron with carboxylate anion at the periphery can produce a hydrophobic interior in aqueous solution (Fig.…”
Section: Future Prospectmentioning
confidence: 99%
“…7). Water-soluble dendrimers with photoresponsive core have already been studied [61][62][63][64][65][66]. It was found that the poly aryl(ether) dendron with carboxylate anion at the periphery can produce a hydrophobic interior in aqueous solution (Fig.…”
Section: Future Prospectmentioning
confidence: 99%
“…We recently reported that stilbene dendrimers with benzyl ether-type dendrons exhibited a volume-conserving isomerization mechanism and a macromolecular effect (or generation effect) on energy transfer efficiency from the peripheral dendrons to the core stilbene in organic solvents [45][46][47] and aqueous solution. [48][49][50] In these cases, the core stilbene unit played an important role as a photo-trigger for large conformational changes (photoisomerization), and as a fluorescent probe for detecting the environment inside the dendrimer. The latter function is based on the high sensitivity to solvent polarity of the 3,3 0 ,5,5 0 -tetrasubstituted stilbene moiety of which the excited singlet state has a charge transfer (CT) character.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, for water-soluble stilbene dendrimers we could afford nanoscale unimolecular compounds which have hydrophobic interior and hydrophilic exterior and found several unprecedented photochemical reactions such as highly selective almost one-way trans-to-cis photoisomerization in water. 6 Aromatic C=C compound with hydrogen bonding also exerted interesting photochemical properties showing one-way trans-to-cis isomerization induced by ultrafast intramolecular hydrogen atom transfer in the excited state. 7 As another approach to functionalizing molecules with C=C double bonds we are interested in introducing potentially ionic salts in photoresponsive compounds such as stilbene.…”
mentioning
confidence: 99%
“…The decrease in quantum yield of trans-to-cis isomerization may have some relation to the polarity and microviscosity. However, despite the high viscosity of 260 cP for [bmim][PF 6 ] compared to that of acetonitrile (0.34 cP), the quantum yield of photoisomerization of trans-TMST seems to be considerably high indicating a nonuniform structure of ionic liquid [bmim] [PF 6 ]. In other word, there is a possibility that viscosity at microlevel seems to be lower than that of bulk state and the ionic liquid [bmim][PF 6 ] molecules should make several different environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation